Study of rising dampness problem in housing area in Klang Valley, Malaysia - Hassan, Muhamad Hanif; Othuman Mydin, Md Azree; Utaberta, Nangkula (Penerbit Universiti Teknologi Malaysia, 2015)
Dampness is a major problem in building. It can leads to old and modern buildings to deteriorate and contribute to building decay. Rising damp is part of dampness that can be categorized as one of the major problem in building particularly in residential building whereas it can affect the building and health of the user. This study was conducted to investigate and examine rising damp problem in landed residential building throughout Klang Valley area. From the site observations, rising damp had been identified during the inspection and investigation. Some of the owner of the affected building does not realized and have knowledge about the problem until this study was carried out at their buildings. Hence, this study identified some of the causes are defective damp proof course, effects of the soils salts in groundwater, humid conditions, water penetrations and piping leakage. Thus, the correct diagnosis and analysis of rising damp problem was carried out to overcome the problems in.